Syngas Generation in a Crossdraft Gasifier System Using a Rice Strew Filter - Yohandri Bow; Isdaryanto Iskandar; Harjadi Gunawan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
One solution to the fossil energy crisis is to use alternative energy, such as coal conversion. Coal may be utilized as an alternative energy source via a variety of methods, one of which being gasification. Gasification is a thermochemical process that converts a solid fuel into a combustible fuel in the presence of less oxygen than is necessary for stoichiometric combustion. One of the gasification methods involves utilizing a crossdraft gasifier system using rice straw as a syngas filter. The goal of this research is to determine the ideal temperature for producing syngas with the highest efficiency through the gasification process. According to study, the most ideal temperature for producing excellent quality syngas is acquired at 750°C with syngas concentration of CH4 1.99%, CO 7.97%, CO2 9.03%, H2 6.82%, O2 12.11%, 62.08% N2 and 16.56% efficiency reached at 650oC.